Legal Analysis of the Form Deed of Sale and Purchase Agreements and the Disposal of Land Rights as the Basic Right to Apply Broking Which Has Expired - Axel Budi Putra; Maryanto Maryanto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to analyze: 1) The validity of Deed of Sale and Purchase Agreements form and Release of Land Rights as the foundation for the right over Broking which the period has expired. 2) Barriers and Solutions for the right over Broking which the period has expired. This study is Social Legal research, this study will be presented on the implementation of the deed of waiver to apply transitions and changes in land rights that have expired. Are analytical, because of data obtained was conducted qualitative data analysis.The research results are: 1) the Deed of waiver in this case not only as an authentic act which has been agreed by both parties, but also the legal consequences which are land-status building rights on which the period expires is released into state land and requested back with the new rights by the applicant. Applicant was granted a priority by the state to reapply new rights to the land that is the property that has a definite legal certainty. 2) Constraints that occur is the deed of relinquishment of rights is used as a pedestal right to request building rights that have expired can not start if the deed of release was made prior to the issuance of the Certificate of Registration of Land (SKPT) of the local Land Office,Keywords: Deed; Deed of Release; Broking.